PENGARUH UMUR TANAMAN TERHADAP DIMENSI POHON SENGON (Paraserianthes falcataria. L) PADA KETINGGIAN TEMPAT TUMBUH YANG BERBEDA - Aning Munir (Fakultas Kehutanan Universitas Winaya Mukti, 2018)
Sengon (Paraserianthes falcataria) can grow from beach to 1600 m sal. The influence of P. falcataria growth cannot be studied because the growth and development of a species is determined by genetic factors (G), environmental factors (E), and interactions between environmental and genetic factors (G + E). The objects of studies is the effect of plant age and altitude of the growing place against the dimension of P.falcataria and obtain the age of plant and altitude that produce the best tree dimension. The research method used experiments using Split Plot with two factors. The main plot factor is the height of the P. falcataria growing site. Results of studies were an interaction between the heights of the place with the age of P.falcaria plants against the volume of P. falcataria. The interaction of the total height and diameter based on the altitude of 825 m sal and the age of P. Falcatia 9 years produced the highest volume of P. falcataria with age of 7 years.